Modified all-suture fixation technique for anterior dislocation following conservative treatment of sternoclavicular joint injury: a case report - Wang, Jiang-Long; Yuan, Zhi-Min; Wen, Jing-Rong; Li, Kang (Frontiers in Surgery, 2026)
Anterior dislocation of the sternoclavicular joint accompanied by articular disc avulsion following conservative treatment is a rare condition. A 58-year-old male suffered a shoulder acromioclavicular joint dislocation and a sternoclavicular joint injury without dislocation after being hit by a heavy object. Two weeks after the sternoclavicular joint was suspended, anterior dislocation occurred. He underwent a stable reduction using a modified all-suture fixation technique. At one-year follow-up, radiological assessment demonstrated maintained anatomical alignment and stable fixation, with complete restoration of daily activities and occupational function. The final Constant-Murley Score was 91, reflecting excellent functional recovery, and the patient reported high satisfaction. This case demonstrates that the modified all-suture fixation technique may offer reliable stabilization and favorable clinical outcomes in the treatment of anterior sternoclavicular dislocation associated with articular disc avulsion.